The Managerial Leadership of Principal in Improving the Teachers` Performances - Wicoksono, Deni Fajar; Yusrizal, Yusrizal; Usman, Nasir (Jurnal Pendidikan Indonesia, 2022)
The quality of education can increase because of teachers` optimal performance. However, teachers` performance and work discipline are currently still low. This study analyses the principal's managerial leadership in improving teachers` performance. This study uses a qualitative approach with a descriptive method. Methods of data collection using observation, interviews, and documentation. The subjects in this study were principals, vice principals, teachers, and supervisors. Data analysis techniques by reducing, presenting, drawing conclusions and verifying data. The results of the study indicate that managerial competence has been implemented well. Principals have programs including school learning planning, teacher supervision, collaboration, work meetings, and workshops. Obstacles faced by principals are teacher discipline, lack of teacher participation in program activities, and many elderly teachers. To anticipate the obstacles in the field, the principal has tried to carry out his duties optimally. The principal's managerial role is quite good, and it is just that teachers need special training to improve teacher performance. So it can be concluded that the principal's managerial leadership improves teacher performance. The implications of this research are expected to improve the managerial leadership of school principals so that teacher performance can increase, and learning objectives can be achieved.